Innovation in MSMES through collaborative networks and the use of ICTs - Silva-Giraldo, Cesar Augusto; Rueda-Mahecha, Yohanna Milena; Moreno-Suarez, Angelica María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The article presents the innovation of MSMEs from the maturity models in smart cities and the implementation of collaborative networks and the use of ICT, presenting an opportunity for sustainable growth, according to the new technologies achieving computerize, interconnect and provide intelligence to the basic systems of organizations through the articulation of the smart city, resulting in the interrelations and circulation of knowledge, which are adapted to give a look based on technologies and infrastructures that, through the use of data and information, aim to provide solutions to problems and achieve an efficient management of cities.